Mediasi Pengelolaan Remitansi pada Pengaruh Tingkat Pendidikan Terhadap Kesejahteraan Pekerja Migran Indonesia - Azzahra Ramadhanti, Nyimas Keizsa; Siwi Agustina, Tri (Teewan Journal Solutions, 2025)
Discussing the welfare of international migrant workers is very interesting, especially when it comes to education level and remittance management. Trenggalek Regency, known as one of the cities in East Java that is the enclave of Indonesian Migrant Workers. The research sample was 330 Indonesian Migrant Workers in Watulimo District, Trenggalek Regency. Data collection was done through questionnaires and hypothesis testing using Path Analysis. The results showed that (1) the characteristics of education proved influential in improving the welfare of Indonesian Migrant Workers in Watulimo District, Trenggalek Regency. (2) Remittance management has been shown to have an effect on improving the welfare of Indonesian Migrant Workers in Watulimo District, Trenggalek (3) Remittance management is proven to partially mediate the influence of educational characteristics on the welfare of Indonesian Migrant Workers in Watulimo District, Trenggalek Regency.